A psychosocial study of young adults' experiences of their sibling's mental illness - Laurie, Gina (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
There are a number of studies that investigate the experiences of mental illness in the context of sibling relationships. However, these studies have not focused on young adulthood and limited research has been conducted in South Africa. This research uses a psychosocial framework which combines psychoanalytic theory and social constructionism to account for individual subjectivity and social influences. This method sought to answer two main research questions: how do young adults construct their experiences of having a sibling with a mental illness and with what effects, and how might we understand the emotional investments in these constructions? Six participants were interviewed and the findings suggest that participants draw on four main discourses in constructing their siblings' mental illness: a discourse of mental illness as a sickness, a discourse of mental illness as part of the person, a discourse of mental illness as bad behaviour, and a discourse of mental illness as a spiritual issue. These discourses and the function of these discourses are discussed. Furthermore, an extract from one participant is examined in a case study format so as to explore the emotional investments in the discourse of mental illness as bad behaviour, arguing that her investments in this discourse serves to protect her by enabling her to manage feelings of not being 'good enough'.
Keywords: Brothers and sisters of people with disabilities -- South Africa -- Case studies; Brothers and sisters of people with disabilities -- Psychology; Mentally ill -- Family relationships; Mentally ill -- Care -- South Africa